JURNAL ALGOR RANCANG BANGUN ALAT PENGHITUNG JUMLAH PRODUKSI DENGAN MENGGUNAKAN MICROCONTROLLER LOAD CELL BERBASIS WEB SERVICE - Adrian Sunata; Rino Rino (ALGOR, 2020)
The industrial world is currently entering the era of the industrial revolution 4.0 where the revolutionary era is an industrial era that collaborates the use of digital information technology and automation technology. One of the things that must be considered to advance the industrial world is the production activities in an industry. From this research to simplify and maximize performance in production activities, the industry needs to use automation technology by using Load Cell weight sensors and other microcontrollers to calculate the results of production activities which then the results of these calculations will be automatically recorded into a database on the web. This certainly adds value to the efficiency of the industrial environment where industrial production activities have a good influence on time efficiency and reports of the results of production activities.